A Common Purpose? Social Work Students’ Social Justice Related Views in Finland and the island of Ireland - McFadden, Paula (Oxford Univeristy Press, 2025)
Exploring social work students’ views to understand how equipped they are to pursue the social justice mission of the profession should be of central academic and practical interest. There are, however, surprisingly few empirical studies focussing on social work students’ views on social justice-related issues from a comparative viewpoint. Such knowledge is thought to be of a wider international interest from a number of perspectives, including social work education and student exchange and, in a wider context, for the development of social work as a profession and for discussing the prerequisites for shared international notions of social work. This article explores the views of social work students studying in different socio-economic contexts and welfare regimes in relation to some key aspects assumed to be vital for the profession. The results based on survey data from student cohorts in Finland (N = 608) and the island of Ireland (N = 279) support the general conclusion that there are important, similar patterns of motivations and understandings amongst the students, despite substantial differences in histories, welfare state developments, current policies and social conditions in various jurisdictions. The results are of interest to educators across countries internationally and provide an important basis for future similar studies.